2011
DOI: 10.4067/s0717-75182011000200005
|View full text |Cite
|
Sign up to set email alerts
|

EL OSTIÓN DEL NORTE CHILENO (Argopecten Purpuratus), UN ALIMENTO DE ALTO VALOR NUTRICIONAL

Abstract: INTRODUCCIÓNLa acuicultura en Chile se ha transformado, en las últimas décadas, en una importante actividad económica. Destaca, sin lugar a dudas, la acuicultura del salmón por sus altos volúmenes de producción y relevancia internacional (1). Sin embargo, existen otras actividades acuicultoras, principalmente de moluscos bivalvos, como es el caso de los choritos, las ostras y el ostión, entre los más importantes (2). Cada uno de ellos tiene caracterís-ticas particulares desde el punto de vista organoléptico y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
6
1
7
Order By: Relevance
“…Moisture analysis showed that O. hubbsorum B has 64.15% of water, being 35.85% dry matter (Table 1). In comparison with other studies performed by Cabello et al; [5] and Valenzuela et al, [24] on different mollusk species, O. hubbsorum B contains less moisture than any mollusk analyzed by these authors whose results showed that O. Vulgaris contains 79.65% of water. This means that the amount of nutrients contained in O. hubbsorum B is greater per unit of weight than the one that could be found in other species, which represents an advantage since it would be possible to get higher levels of nutrients with smaller food portions.…”
Section: Moisture Contentcontrasting
confidence: 38%
See 2 more Smart Citations
“…Moisture analysis showed that O. hubbsorum B has 64.15% of water, being 35.85% dry matter (Table 1). In comparison with other studies performed by Cabello et al; [5] and Valenzuela et al, [24] on different mollusk species, O. hubbsorum B contains less moisture than any mollusk analyzed by these authors whose results showed that O. Vulgaris contains 79.65% of water. This means that the amount of nutrients contained in O. hubbsorum B is greater per unit of weight than the one that could be found in other species, which represents an advantage since it would be possible to get higher levels of nutrients with smaller food portions.…”
Section: Moisture Contentcontrasting
confidence: 38%
“…Protein content was found to be 69.38% (Table 1), so O.hubbsorum B may be considered a good source of proteins in comparison with other species such as O. vulgaris from the Colombian Pacific or different mollusks studied previously for other authors [5,24]. This suggests, not only the high nutritional value of this species but also, a large difference within octopus species [5].…”
Section: Protein Contentmentioning
confidence: 83%
See 1 more Smart Citation
“…El consumo de productos del mar en Chile no supera los 6,9 kg per cápita al año y el de mariscos es inferior (Villena 2012). Entre los mariscos, los moluscos del grupo de los bivalvos, son los de mayor consumo debido a que se les reconoce como alimentos de alta calidad nutricional (Valenzuela et al 2011). Los bivalvos en general contienen entre 10 y 20 g de proteína total por 100 g de carne, con una calidad nutricional similar a la carne de vacuno y al huevo (Schmidt-Hebbel et al 1992, Miranda 2000, USDA 2015.…”
Section: Introductionunclassified
“…Los bivalvos en general contienen entre 10 y 20 g de proteína total por 100 g de carne, con una calidad nutricional similar a la carne de vacuno y al huevo (Schmidt-Hebbel et al 1992, Miranda 2000, USDA 2015. Además, son fuente importante de minerales, oligoelementos y vitaminas (Schmidt-Hebbel et al 1992, Valenzuela et al 2011. El contenido graso en los moluscos frescos es bajo (<2%) (Schmidt-Hebbel et al 1992, USDA 2015; sin embargo, destaca su aporte de ácidos grasos (AG), en particular los poliinsaturados como el eicosapentaenoico (20:5n-3, EPA) y el docosahexaenoico (22:6n-3, DHA), que pueden alcanzar hasta un 28% de las calorías derivadas de las grasas (Ersoy & Sereflisan 2010, Valenzuela et al 2011.…”
Section: Introductionunclassified